2020
DOI: 10.3389/fendo.2020.00528
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1281 as a Novel Circulating Biomarker in Patients With Diabetic Retinopathy

Abstract: Objective: Recently, the role of circulating miRNAs as non-invasive biomarkers for the identification and monitoring of diabetes microvascular complications has emerged. Herein, we aimed to: identify circulating miRNAs differentially expressed in patients with and without diabetic retinopathy (DR); examine their predictive value; and understand their pathogenic impact. Methods: Pooled serum samples from randomly selected matched patients with type 2 diabetes, either with or without DR, were used for initial se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Nonetheless, some members of the non-coding genome, comprising micro RNAs (miRNAs) and long ncRNAs (lncRNAs) of 18–25 and over 200 nucleotides in length, respectively, represent the most relevant mechanism of post-transcriptional regulation, and their biology has been put at the center of current basic research. Via binding to 3′-untranslated regions (3′-UTR) of target mRNAs and influencing the decay of transcripts, miRNAs typically act as repressors of gene expression [ 203 ], whereas a variety of mechanisms of action have been described for lncRNAs. These include: (i) direct interaction with DNA, coding RNA molecules and chromatin proteins (i.e., histones); (ii) binding of small RNAs or RNA-binding proteins; (iii) competition with endogenous RNA for binding to miRNAs; (iv) trafficking of RNA-binding proteins to the effector molecules [ 204 , 205 ].…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Nonetheless, some members of the non-coding genome, comprising micro RNAs (miRNAs) and long ncRNAs (lncRNAs) of 18–25 and over 200 nucleotides in length, respectively, represent the most relevant mechanism of post-transcriptional regulation, and their biology has been put at the center of current basic research. Via binding to 3′-untranslated regions (3′-UTR) of target mRNAs and influencing the decay of transcripts, miRNAs typically act as repressors of gene expression [ 203 ], whereas a variety of mechanisms of action have been described for lncRNAs. These include: (i) direct interaction with DNA, coding RNA molecules and chromatin proteins (i.e., histones); (ii) binding of small RNAs or RNA-binding proteins; (iii) competition with endogenous RNA for binding to miRNAs; (iv) trafficking of RNA-binding proteins to the effector molecules [ 204 , 205 ].…”
Section: Epigenetic Modificationsmentioning
confidence: 99%
“…Intraocular neovascularization mediated by VEGF may lead to vitreous hemorrhage, retinal detachment, and eventually blindness [ 9 ], which is closely related to the occurrence and development of DR. Evidence showed that serum VEGF levels significantly elevated in patients with DR [ 10 ]; some factors that affect the occurrence of DR may be achieved by regulating the expression of VEGF [ 11 , 12 ], suggesting that VEGF may play an important role in the development of DR. The human VEGF gene is located on chromosome 6p21.3, whose single nucleotide polymorphisms (SNPs) can affect gene expression by altering key regulatory sequences or by altering mRNA stability at key regulatory loci [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs have not only been identified as relevant players in metabolic disorders but also as potential biomarkers for their detection [ 33 , 34 , 35 ]. For instance, miR-194, miR-148b, miR-223, miR-130a, miR-19a, and miR-1281 were found to be dysregulated in the plasma of patients with T2DM [ 33 , 36 , 37 ]. The non-invasive identification of microRNAs in circulation could prove to be crucial for the detection and assessment of T2DM.…”
Section: Discussionmentioning
confidence: 99%